O desafio de ser agente comunitário de saúde rural no Município de Jerônimo Monteiro-ES : um estudo na perspectiva da análise institucional - Baptistini, Renan Almeida (2012)
An experimentation with an experienced group of eight Community Health Workers who work in rural areas of the City of Jerônimo Monteiro, in the southern of Espírito Santo state. Inspired by the Institutional Analysis, this study aimed to analyze the arrangements in place and instituting the practice of a Rural Community Health Agent. This study, which brings a qualitative approach, made possible, through interviews and observation work done through home visits in rural areas with the Community Health Agents, characterize and understand the daily work of these professionals, as well as the peculiarities and challenges of its workplace – the countryside. Some challenges may be appointed to expertise and knowing how to be the Community Health Agent in rural areas, for example, the vast territory covered by the Family Health Strategy, the wide dispersal of population, the remote places, animals, and distant access or inaccessible to most rural households, especially on rainy days. The City of Jerônimo Monteiro is characterized by an agrarian situation typical of Espírito Santo, where small farms predominate crossed by dirt roads. In this context, the Community Health Workers Rural seek, through viable alternatives, fulfilling their actions instituted and realize, through the uniqueness of other atypical spaces – a kraal, for example – to reinvent the new.